Beyond 2020 - Strategies and Costs for Transforming the European Energy System - Brigitte Knopf; Yen-Heng Henry Chen; Enrica De Cian; Hannah Förster; Amit Kanudia; Ioanna Karkatsouli; Ilkka Keppo; Tiina Koljonen; Katja Schumacher; Detlef van Vuuren (Fondazione Eni Enrico Mattei (FEEM), 2014)
The Energy Modeling Forum 28 (EMF28) study systematically explores the energy system transition required to meet the European goal of reducing greenhouse gas (GHG) emissions by 80% by 2050. The 80% scenario is compared to a reference case that aims to achieve a 40% GHG reduction target. The paper investigates mitigation strategies beyond 2020 and the interplay between different decarbonization options. The models present different technology pathways for the decarbonization of Europe, but a common finding across the scenarios and models is the prominent role of energy efficiency and renewable energy sources. In particular, wind power and bioenergy increase considerably beyond current deployment levels. Up to 2030, the transformation strategies are similar across all models and for both levels of emission reduction. However, mitigation becomes more challenging after 2040. With some exceptions, our analysis agrees with the main findings of the Energy Roadmap 2050 presented by the European Commission.
Keywords: Q2; Q4; 330; European Decarbonisation; Mitigation Scenarios; Model Comparison; Climate Change; EU Energy Roadmap 2050